2013
DOI: 10.1186/1471-2458-13-475
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of hazardous drinking, tobacco smoking and physical inactivity in vocational school students

Abstract: BackgroundTobacco smoking, hazardous drinking and physical inactivity during adolescence are risk factors that are associated with poorer health in adulthood. The identification of subgroups of young people with a high prevalence of one or more of these risk factors allows an optimised allocation of preventive measures. This study aimed at investigating hazardous drinking, tobacco smoking and physical inactivity as well as their associations and demographic predictors in vocational school students.MethodsOut o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 28 publications
6
60
1
3
Order By: Relevance
“…Generally, our findings are in line with other studies. For instance, our results are supported by research among young people (15–21 years and older) in Switzerland, where multiple risk factors were observed in a substantial proportion of young people (12). Likewise, our four clusters of BRFs resonate with an Irish study among the general population, where research of health behavior clustering in a nationally representative adult sample observed six clusters (20).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Generally, our findings are in line with other studies. For instance, our results are supported by research among young people (15–21 years and older) in Switzerland, where multiple risk factors were observed in a substantial proportion of young people (12). Likewise, our four clusters of BRFs resonate with an Irish study among the general population, where research of health behavior clustering in a nationally representative adult sample observed six clusters (20).…”
Section: Discussionsupporting
confidence: 85%
“…CA is premised on shared characteristics to categorize a given population into mutually exclusive subgroups (clusters) for which the properties or patterns within a cluster are similar to each other than they are to properties within a different cluster (10, 11). Indeed, researchers have voiced that most health behavior research has adopted an approach where behaviors were studied in isolation and traditionally focused on individual risk behavior/s, in segregation from other BRFs (4, 7), despite that BRFs co-exist together and are related to one another (12). Limited research has explored clustering of lifestyle BRFs; and the studies that undertook such approach rarely focused on university students.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these CVD risks are worse when smoking and drinking occur together. Particularly, previous studies involving university students have shown that the smoking/tobacco use and drinking habits formed during this adulthood period and these hazard habits can affect CVDs (Haug et al, 2013;Mukamal, 2006;Steptoe et al, 2002;Wicki et al, 2010). For example, the combination of smoking and drinking was often in university male students in a recent Swedish study (Haug et al, 2013) and in review articles among European student populations (Wicki et al, 2010).…”
Section: Variablesmentioning
confidence: 97%
“…Although some studies have investigated the relationship between health and lifestyle factors (i.e. drinking, smoking, and physical activity) among international students (Haug, Schaub, Salis Gross, John, & Meyer, 2013;Pan, Wong, Joubert, & Chan, 2007;Steptoe et al, 2002;Wicki, Kuntsche, & Gmel, 2010), most of these studies were conducted in Western countries and the study participants were mostly international students from China, Taiwan, or Vietnam Do & Cho, 2009;Ying, 2005). Furthermore, there is a limited amount of research regarding health-promoting lifestyles and cardio-metabolic risks among international students in Asian countries such as Korea (Yan & Cardinal, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…11 Smoking prevalences are particularly high in adolescents and young adults with lower educational levels. 14 …”
mentioning
confidence: 99%